Morphometric characterization of del Molle Basin applied to the evaluation of flash floods hazard, Iglesia Department, San Juan, Argentina - Perucca, Laura Patricia A. (2011)
One of the main geological hazards that affect the Iglesia department is flash floods, produced by heavy seasonal rains, characterized by their high velocities and destructive power. These streams are generated in the watersheds of the mountainous region of the Cordillera Frontal. The del Molle basin was selected as a suitable case to evaluate the potential magnitude of flash floods in relation to their associated hazard level in Malimán de Arriba, located directly at the confluence of the tributaries with the Blanco River. This paper evaluates some of the hydrological aspects of a torrential regime basin that caused severe damage in Malimán during January 2010. This work analyzes different morphometric characteristics of the El Molle basin in order to evaluate the flash flood hazard. For this purpose, the basin is divided into four sub-basins and some basic parameters (surface, perimeter, basin length, elevations and slope of the main riverbed) are calculated. These parameters allow approximate prediction of the behavior of the basin in the presence of a series of theoretical rainstorms which may generate unusual runoff volumes. The predicted flash floods were compared against the Malimán flash flood.